Perspektif Hukum Perdata Indonesia dan Hukum Kanonik terhadap Perceraian dalam Komunitas Katolik - Larantukan, Rafael Suban; Latumahina, Rosalinda Elsina (CV. Era Digital Nusantara, 2025)
The objective of this study is to analyze the legal validity of divorce within the Indonesian Civil Law system and Canon Law of the Catholic Church, as well as to identify its legal implications for Catholics in Indonesia. Under Indonesian Civil Law, divorce is considered valid based on specific grounds such as adultery, domestic violence, and continuous disharmony. In contrast, Canon Law of the Catholic Church views marriage as a perpetual sacrament that cannot be dissolved except through an annulment, which requires specific conditions. This study employs a normative juridical approach using legal analysis through literature reviews and relevant legislation. The findings reveal that the conflict between civil law and canon law significantly impacts the social, moral, and spiritual aspects of Catholics. Divorce under civil law is often not recognized by the Church, leading to divorced individuals being considered still bound by the sacrament of marriage. This situation creates social stigma and alienation from the church community, as well as limits their access to certain sacraments.